2013
DOI: 10.1016/j.neuropharm.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of M1 muscarinic receptor/G-protein interaction by amyloid β1–42

Abstract: The overproduction of β-amyloid (Aβ) fragments in transgenic APPswe/PS1dE9 mice results in formation of amyloid deposits in the cerebral cortex and hippocampus starting around four months of age and leading to cognitive impairment much later. We have previously found an age and transgene-dependent weakening of muscarinic receptor-mediated transmission that was not present in young (6-10-week-old) animals but preceded both amyloid deposits and cognitive deficits. Now we investigated immediate and prolonged in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 66 publications
0
23
1
Order By: Relevance
“…M1 mAChRs are required for non-amyloidogenic AβPP processing [3, 5, 6]. To determine whether M1 mAChRs are involved in the maintained nonamyloidogenic processing, control (N=7) and MS (N=6) rats were treated in vivo with dicyclomine, the M1 mAChR antagonist previously shown to exacerbate Aβ pathology in 3xTgAD mice [28], and αCTF and βCTF protein levels were measured in synaptosomal fractions by Western blot.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…M1 mAChRs are required for non-amyloidogenic AβPP processing [3, 5, 6]. To determine whether M1 mAChRs are involved in the maintained nonamyloidogenic processing, control (N=7) and MS (N=6) rats were treated in vivo with dicyclomine, the M1 mAChR antagonist previously shown to exacerbate Aβ pathology in 3xTgAD mice [28], and αCTF and βCTF protein levels were measured in synaptosomal fractions by Western blot.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, there is direct evidence that M1 muscarinic acetylcholine receptors (M1 mAChRs), which are the most abundant muscarinic receptor in cerebral cortex and hippocampus, play a critical role in cognition and AD pathogenesis [24]. Interestingly, activating M1 mAChRs elevates soluble amyloid precursor protein α (sAβPPα), and decreases Aβ plaques and NFTs [3, 5, 6]. On the contrary, pharmacological inhibition or genetic deletion of M1 mAChRs from 3xTgAD mice, which have cholinergic dysfunction, exacerbates cognitive impairments and increases the density of Aβ plaques and NFTs and the magnitude of gliosis [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Global KOs of m1, G q , and Src are known to affect NMDARdependent LTP induction in mice (15,42,43). Furthermore, cholinergic lesions impair the signaling pathway (18,21,44), and the overproduction of β-amyloid causes uncoupling of m1 receptor/ G protein interaction (45). Thus, deficits in the signaling pathway most likely contribute to the loss of cognitive function in AD.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent results suggest that a decrease in I M (the potassium current activated by muscarinic receptor stimulation) may be an integral part of AD pathophysiology (Leao et al, 2012; Duran-Gonzalez et al, 2013), explaining why I M blockers fail to improve cognition in AD clinical trials (Rockwood et al, 1997). Evidence also points out that the initial injurious effects of the fragment of Aβ, Aβ 1 - 42 , on M1 muscarinic receptor-mediated transmission is due to compromised coupling of the receptor with G q/11 G-protein (Janickova et al, 2013). Nicotinergic neurotransmission has also been involved in AD early stages, not only through an activation of presynaptic α7-nicotinic acetylcholine receptors (α7-nAChR; Dougherty et al, 2003) but also by interaction with GABAergic (Spencer et al, 2006) and glutamatergic (Wang et al, 2009) systems.…”
Section: Aβ and Excitatory Neurotransmissionmentioning
confidence: 99%
“…Therefore, it is plausible an Aβ-induced intracellular signaling impairment which compromises this effector system. In fact, Aβ has been shown to disrupt G protein-coupled receptors function (Thathiah and De, 2011), and compromise coupling of the receptor with G protein (Janickova et al, 2013) as well as several different secondary messenger systems (Thathiah and De, 2009; Yang et al, 2011; Fu et al, 2012; Zhang et al, 2014). In addition, we have recently showed that Aβ decrease GABA B currents in CA3 pyramidal neurons, a putative mechanism of Aβ-induced synaptic dysfunction observed in the septohippocampal system, which likely occur directly on GirK channels (Nava-Mesa et al, 2013).…”
Section: Aβ and Gabaergic Neurotransmissionmentioning
confidence: 99%